Responding to irregular migration: High potential of local governments in Turkey - Genç, Hatice Deniz (Wiley, 2018)
This study examines local governments' growing presence in irregular migration management, and discusses how autonomous local responses challenge centralist approaches to the management of this migration. By building on the relevant legal framework, secondary literature and interview notes, the study focuses its attention on irregular migration in Turkey, and uncovers the potential of two local government units - district municipalities and muhtarlks - in the response to irregular migration. The study discusses the enablers and the main constraints on these local government units in responding to, and therefore involving themselves in, the management of the phenomenon. As discussed in the study, the main impediment appears to be the country's highly centralized state structure, while there also exist several enablers, such as Turkish Townsmen Law (Hemehri Hukuku), the trust relationship with their inhabitants, and their experience of liminality in handling irregular matters and providing social aid to vulnerable, fragile and low-income residents.
WOS: 000432001300006
Keywords: Local Governments; High Potential; Irregular Migration; Turkey